Price-based unit commitment using Muller method - Tabunot, Arvin M.
This project has developed a solution to price-based unit commitment of generating units using a non-traditional approach called Muller method. The problem formulations uses an objective function that maximizes the profit of a generating company in a deregulated market, by optimally committing its portfolio of generating units A program implements the proposed method using GNU Octave. The proposed method is tested on 3- and 10- unit systems, and on a 14-unit Philippine generator company and one day forecast from the Wholesale Electricity Spot Market. The stimulation results show that the approach works well for systems with a small number of generating units. Because of the minimal computation time, the approach is amenable for use in real-time generation scheduling for electricity market operation.